Critical analysis of the system of capital gains taxation in Cameroon - Christiane, Tedongmo Petseteye (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2015)
Capital gains tax (CGT) as a fiscal tool, has over the last century, become embedded in many tax systems around the world. It has been consistently used to overcome loopholes exploited by taxpayers taking advantage of the absence of CGT in many tax systems. As regards the importance of the tax as a means of tackling avoidance schemes, the theoretical framework for imposing this tax has played an important role in streamlining national approaches to capital gains taxation and it has impacted on capital structure and investment decisions of taxpayers. After more than three decades of its introduction, whereby many reforms have taken place, the current study proceeds to an evaluation of the impact of these reforms on the overall system of taxing capital gains in the country. The present study thus analyses the system of capital gains taxation in Cameroon with the objective of proposing reforms that could be used for improving current CGT practice. It focuses on the implementation of CGT in the country except for capital gains realised on the stock exchange. It contends that the lack of comprehensive tax provisions and incentives is the cause of tax evasion. Thus from the analysis of the reasons for the introduction of CGT and the issues involved in evaluating CGT systems, and examination of some overseas experiences, some survey questions were drafted to solicit the view of the main players. The study thus bridges the gap between the theoretical examination of the CGT system in the country and the perception and experience of the tax system by some stakeholders. The “mixed method” design has been adopted in the study, involving both quantitative (survey) and qualitative (interview) in analysing the data of overall stakeholders' perception of the CGT in Cameroon and the areas that need to be improved. The findings of the study reveal the lack of clarity, some forms of inconsistency and the lack of incentives in imposing CGT. From the total of respondents, 75% supported the need for implementing some reforms in the methods of imposing the tax. The approaches to imposing CGT in India, Australia, Malaysia and France have served well; as a guide for proffering reforms. It thus illustrates the adaptability of the CGT practice of these countries to Cameroon with an emphasis on the practice in France. In line with the objective of reforming the current system, the redefinition of the factor triggering CGT on real estate transaction and the utilisation of the holding periods as a means to reduce speculation and induce the realisation of real estate gains were advocated. The exemption of the gains realised from the transfer of the residential house was suggested as a means to promote home ownership. With regard to the recent increase of CGT on shares transfer, a discount system based on the length of ownership was advocated as a means to provide a solution to the lock- in effect that may result from such increase coupled with the classical system of taxing corporate profits. Finally, with regard to the gains from business, redirecting the rollover reinvestment incentives which was deleted by section 8 of the GTC has been proposed to be restored but granted exclusively to SME provided it complies with the holding periods proposed. In the same vein, more flexibility was suggested with regard to the criteria of exemption in case of rollover reinvestment of accrued gains from the process of re-evaluation of business assets. The study represents a contribution to the existing literature towards improving the CGT system of Cameroon. It is hoped that the findings revealed in this study may assist in the process of reforming the current approach to imposing CGT in the country.